The gap between primary and secondary schools teachers in followership style at ADNI Islamic School, Malaysia - Al Anshory, Ahmad Suhail; Mohd Ali, Hairuddin (2013)
The purpose of this quantitative research was to investigate the gap between primary and secondary school teachers in followership style at Adni Islamic School, Malaysia. Surveys were completed by 92 teachers from both respective schools which included the completion of the related questionnaire. The findings of this research show that all Kelley’s Followership Styles (exemplary, alienated, pragmatist, conformist and passive) represent the followership style of primary and secondary school teachers at AIS. The most practised followership style is exemplary which amounted to 39 (42.3%) of teachers. Furthermore, the findings show that there was a significant difference in followership styles between the male primary and secondary school teachers of AIS. On the contrary, there was no any significant difference of followership styles between the female primary and secondary school teachers of AIS. In general, there was no any significant difference of followership styles between both schools. Based on the findings of this study, it is recommended that the respective educational organization structures maintain the domination of exemplary followership style and enhance followership, since it is especially related to help followers achieve exemplary level that is be expected to promote higher levels of organization performance. Suggestions concerning further research on the subject of followership are presented.